Pengelolaan Harta Masyarakat Kelas Menengah Muslim Kota Medan Dengan Pendekatan Islamic Wealth Management - S Sugianto (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2019)
Management of wealth in the Islamic economy becomes important especially because the main economic problem in the Islamic economy is the unequal distribution of resources (assets). This research aims to describe the creation and development, preservation and protection, expenditure and distribution of assets of the new Muslim middle class in Medan. This research uses a qualitative approach with descriptive methods. Data was collected through interviews and document studies. Data analysis uses descriptive qualitative analysis. The results showed that business planning and investment planning were mostly carried out by the Medan Muslim middle class. It's just that the use of LKS is still low. While planning for the protection of assets through Islamic financial institutions is still low, so is financial planning through Islamic financial institutions is still low; family financial planning is also quite good but the use of Islamic financial institutions is still low; and religious financial planning has not been an effort as well as in the use of Islamic financial institutions which are still low.